2019
DOI: 10.1108/bij-05-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable manufacturing system: a state-of-the-art review

Abstract: PurposeThe purpose of this paper is to present an organized review of existing research on reconfigurable manufacturing system (RMS). The paper considers majority of the prominent research articles in the domain of RMS published ever since RMS was envisaged in 1997.Design/methodology/approachThe paper systematically reviews, classifies and analyses the published literature on postulations and design of RMSs. The general observations from the literature and research gaps recognized thereon are highlighted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…They identified most frequently used solution approaches for optimization problems along with their classification. Also, Khanna (2019) conducted state-of-the-art review of RMS articles in order to classify and analyze them. He revealed several aspects related to RMS research and concluded that the field needs more focus for its growth.…”
Section: Background Of Rmsmentioning
confidence: 99%
“…They identified most frequently used solution approaches for optimization problems along with their classification. Also, Khanna (2019) conducted state-of-the-art review of RMS articles in order to classify and analyze them. He revealed several aspects related to RMS research and concluded that the field needs more focus for its growth.…”
Section: Background Of Rmsmentioning
confidence: 99%
“…Reconfigurable manufacturing system is one of the NGMS, which is designed to be responsive towards the unintended changes in product demands and variety. Several reviews of RMS are conducted in the literature in an attempt to organise the existing body of research in this field, like: Yelles-Chaouche et al ( 2020), Khanna and Kumar (2019), Bortolini et al (2018), Koren et al (2018),…(Yelles-Chaouche et al 2020), a review of the RMS literature is presented, based on the optimisation problems studied and the approaches proposed. The authors classified the studies into four categories, namely RMS design, production planning and scheduling, layout design, and line balancing and re-balancing problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors classified the studies into four categories, namely RMS design, production planning and scheduling, layout design, and line balancing and re-balancing problems. In the literature review presented in Khanna and Kumar (2019), a focus is made on the RMS responsiveness, the RMS conceptual developments, the part family formation, and RMS design problems. Koren et al (2018), devised the operational and the design principles for RMS and then according to the formulated principles, the literature review of RMS design and operation research problems is presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature reviews have also been conducted (e.g. [3,25]) remarking that both the design and operation domains need further research. The main conclusion similar in all reviews is the need for practical guidelines driving industrial companies in the transition toward the RMS paradigm.…”
Section: The Two Domains Of Research On Rmsmentioning
confidence: 99%